Impact of Milk Consumption and Dietary Patterns on Pelvic Organ Prolapse: A Mendelian Randomization Study - Xia X; Hu Y; Xu J; Fan S; Zhang Y (International Journal of Women's Health, 2025)
Xinglu Xia,1 Yiqin Hu,1 Jingui Xu,1 Suhong Fan,1 Yunfeng Zhang2 1Department of Gynaecology, The Quzhou Affiliated Hospital of Wenzhou Medical University, Quzhou People’s Hospital, Quzhou, 324000, People’s Republic of China; 2Department of Anaesthesiology, The Quzhou Affiliated Hospital of Wenzhou Medical University, Quzhou People’s Hospital, Quzhou, 324000, People’s Republic of ChinaCorrespondence: Yunfeng Zhang, Department of Anaesthesiolog, The Quzhou Affiliated Hospital of Wenzhou Medical University, Quzhou People’s Hospital, No. 100, Minjiang Avenue, Kecheng District, Quzhou, Zhejiang, 324000, People’s Republic of China, Tel +86-13157001161, Email yfz1161@163.comBackground: Pelvic organ prolapse (POP) severely impacts women’s quality of life and disrupts their daily routines. This study uses two-sample Mendelian randomization (MR) to explore the causal link between dietary habits and POP, providing useful insights for its treatment.Materials and Methods: We used genome-wide association (GWAS) data from Europeans for our study. Two-sample MR analysis was utilized to explore the potential causal relationship between dietary habits and the risk of POP. Five distinct MR methods were applied, with the primary results derived from the inverse variance weighted (IVW) method. Additional sensitivity analyses were performed to assess potential horizontal pleiotropy and heterogeneity in the findings. Moreover, a two-step MR design was used to examine possible mediating factors within dietary habits.Results: Seventeen dietary habits were identified as having a significant causal relationship with the risk of POP (p < 0.05). Notably, consumption of processed meat and dairy intake, including both whole and skim milk, were found to be associated with an increased risk of POP. Two-step MR analysis indicated that high-density lipoprotein cholesterol (HDL-C) may play a crucial role as a mediating factor between regular milk consumption and POP, contributing to 7.5% of the effect of whole milk consumption and 4.1% of the effect of skim milk consumption. Importantly, sensitivity analyses further validated the robustness of our findings.Conclusion: Our findings offer compelling evidence of the causal relationship between dietary habits (especially dairy and processed meats) and the risk of POP, providing valuable recommendations for POP patients in making informed dietary decisions. Keywords: pelvic organ prolapse, Mendelian randomization, dietary habits